Adaptation among aged care and disability service providers in response to the COVID-19 pandemic: Lessons for the future - Seivwright, Ami; Kaleveld, Lisette; Meltzer, Ariella; Atkins, Mariana; Varadharajan, Meera; Campbell, Perri; Callis, Zoe; Wilson, Erin (Frontiers in Health Services, 2022)
Aged care and disability service organizations are critical infrastructure. However, in 2020, restrictions were introduced to reduce the infection risk of the coronavirus disease 2019 (COVID-19), and these organizations needed to quickly devise COVID-safe ways of working to continue to meet the needs of their clients. To investigate how these organizations adapted their service delivery and which innovations they felt were worthwhile for sustaining beyond the COVID-19 pandemic, interviews were undertaken with representatives from 26 aged care and disability service organizations across three states in Australia (Western Australia, New South Wales, and Victoria). Findings revealed that organizations adapted their practices across three key innovation areas: (1) developing new approaches or expanding existing services, particularly around food provision, social connection, information dissemination, and technology support; (2) modifying the mode of service delivery, through safe in-person contact or offering alternative online services; and (3) reducing bureaucracy and introducing remote working. A common theme across all service innovations was the strong focus on providing clients and staff with choice and control. Moving forward, many organizations wanted to integrate and maintain these innovations, as they were associated with additional benefits such as increased client health and safety, service flexibility, and sufficient human resources to serve clients. However, continued maintenance of some initiatives require additional resourcing. The continuation of COVID-19 pandemic adaptations and, indeed, ongoing innovation, would therefore be facilitated by greater flexibility of funding to allow organizations and their clients to determine the service types and modes that best meet their needs. Further, these innovations have implications for sector-wide best practice.